Activities and projects of the Bibliographical Data Working Group (DARIAH-EU) - J. M. Łubocki; E. Herden; D. Siwecka (Библиосфера, 2021)
The material aims to introduce the Bibliographical Data Working Group – part of the Digital Research Infrastructure for the Arts and Humanities (DARIAH-EU) – and to feature projects fulfilled by this group. This working group since 2019 brings together specialists (as of today: 38 researchers) from a number of different countries and the main goals of the group are to foster the development of cooperation between bibliographies and serve as a platform for knowledge exchange aimed at bringing together creators of bibliographical data, scholars interested in using those resources in data-driven research, and theorists of bibliography and documentation. In the presentation two projects are described in detail: 1. the report “An analysis of the current bibliographic data landscape in the humanities: Bibliodata curation, research, and collaboration; 2. The project “Multilingual encyclopaedic dictionary of types of documents”. The purpose of the article is not only to describe these projects but above all to invite Congress members to collaborate on them.